Pengaruh Kualitas Pelayanan, Kualitas Produk, Dan Sistem Bagi Hasil Terhadap Kepuasan Nasabah Tabungan Mudharabah Studi Kasus Bank Syariah Indonesia KC Tanjung - Mahyuni; Ervinia Puspitasari (Indonesian Journal of Applied Accounting and Finance, 2025)
The purpose of this study is to determine the influence of service quality, product quality, and the profit-sharing system on customer satisfaction of mudharabah savings at PT Bank Syariah Indonesia KC Tanjung. This research employs a quantitative method with a systematic investigative approach. Both primary and secondary data were used, with data collected through a questionnaire instrument. The collected data were then processed using SPSS. The results of the study indicate that, partially, service quality and product quality have a significant effect on customer satisfaction, whereas the profit-sharing system does not have a partial effect on customer satisfaction. Simultaneously, service quality, product quality, and the profit-sharing system have a significant influence on the satisfaction of mudharabah savings customers at Bank Syariah Indonesia KC Tanjung.